Pengembangan Modul Bernuansa Pendidikan Karakter yang Dilengkapi Mind Map pada Materi Sistem Peredaran Darah untuk SMA (Jurnal Bioconcetta, 2017)
The aim of this research is to test the validity and practicality biology course module nuanced character education with mind map in circulation system topic for a 2nd grade developed to Senior High School. This research is a development research use four D models that is define phase, design phase, develop phase and disseminate phase. Stage implemented until the develop phase is validity test and practicality test. For validity tested by 6 validators, and for the practicaality tested by 3 teachers and 20 students of SMAN 4 Padang. Data were obtained from questionnaire validation and questionnaire practicality. The results showed that the module developed is very valid (89.72%) and practical by the teacher with the value is 84, 81% and 88,64% by the students